Xiazhui: The Real Person Slash Novel That Triggers The Blockage of AO3 in China - Wang, Aiqing (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2023)
Owing to its dual correlation with homosexuality and eroticism, danmei (Boys Love) in China is subject to state censorship, so in a hit online serial The Untamed adapted from a popular danmei novel, the male-male relationship between protagonists has been expurgated. Obsessed with the romance in the original narrative yet dissatisfied with the officially sanctioned adaptation, fangirls create fanfiction, including real person slash (RPS) based on the leading actor Xiao Zhan and his co-star from the The Untamed. Xiao’s fans reported a piece of RPS titled Xiazhui and Archaic of Our Own (AO3) that hosted it, causing AO3 to be blocked in China on 29th February 2020. Since Xiazhui features real celebrities, it concerns moral debates. Furthermore, Xiazhui pertains to Xiao’s fanbase whose acts are interconnected with toxic fandom and the so-called ‘heresy-style star worship’. More significantly, the contentious aspect of Xiazhui also lies in its homoerotic depictions that are regarded as indecent in a contemporary Chinese context. To cite this article (7th APA style): Wang, A. (2023). Xiazhui: The real person slash novel that triggers the blockage of AO3 in China. Journal Communication Spectrum: Capturing New Perspectives in Communication 13(1), 13-29. https://dx.doi.org/https://doi.org/10.36782/jcs.v13i1.2159